Challenges in Alzheimer's Disease Drug Discovery and Development: The Role of Modeling, Simulation, and Open Data. Issue 4 (11th March 2020) - Conrado, Daniela J.; Duvvuri, Sridhar; Geerts, Hugo; Burton, Jackson; Biesdorf, Carla; Ahamadi, Malidi; Macha, Sreeraj; Hather, Gregory; Francisco Morales, Juan; Podichetty, Jagdeep; Nicholas, Timothy; Stephenson, Diane; et al.
Abstract : Alzheimer's disease (AD) is the leading cause of dementia worldwide. With 35 million people over 60 years of age with dementia, there is an urgent need to develop new treatments for AD. To streamline this process, it is imperative to apply insights and learnings from past failures to future drug development programs. In the present work, we focus on how modeling and simulation tools can leverage open data to address drug development challenges in AD.